In-vivo evaluation of pathogenicity and antimicrobial profile susceptibility from Escherichia coli samples isolated from commercial layer hens - Guastalli, Elisabete Aparecida Lopes; Buim, Marcos Roberto; Guastalli, Bruno Henrique Lopes [UNESP]; Ávila, Fernando Antonio De [UNESP] (Instituto Biológico, 2018)
Antimicrobial sensitivity and pathogenicity level of 90 strains of Escherichia coli isolated from livers and intestines from commercial layer hens presenting diarrhea were analyzed. To evaluate the antimicrobial susceptibility, all samples were subjected to antimicrobial susceptibility testing using 11 commercial drugs. The results have showed none of the strains was susceptible to all antibiotics tested. All samples showed resistance to two or more drugs. According to the mortality rate of the birds, the in-vivo pathogenicity test classifies the strains into four classes: high, intermediate, low and nonpathogenic. The test has showed 23 (25.5%) of the samples were highly pathogenic, 21 (23.3%) of intermediate pathogenicity, 23 (25.5%) low pathogenic, and 23 (25.5%) non-pathogenic. When the results of the classes of pathogenicity from isolates have been associated with antimicrobial susceptibility, nonpathogenic strains were less sensitive to the antibiotic ampicillin and increased sensitive to streptomycin antimicrobial compared to the others classes of pathogenic. Nonpathogenic strains showed resistance to many antimicrobials, an alert for poultry, since these bacteria might acquire the virulence genes and infect birds, others animals and even human beings.

Foram verificados a sensibilidade antimicrobiana e o índice de patogenicidade de 90 amostras de Escherichia coli isoladas do fígado e do intestino de pintainhas de postura comercial com diarreia. Para avaliar a sensibilidade antimicrobiana, todas as amostras foram submetidas ao teste de susceptibilidade antimicrobiana por meio de 11 drogas comerciais. Os resultados demonstraram que nenhuma das estirpes foi sensível a todos os antimicrobianos testados. Todas as amostras apontaram resistência a duas ou mais drogas. De acordo com o índice de mortalidade das aves, o teste de patogenicidade in vivo classificou as estirpes em quatro classes: alta, intermediária, baixa e não patogênica. O teste revelou que 23 (25,5%) das amostras foram de alta patogenicidade, 21 (23,3%) de patogenicidade intermediária, 23 (25,5%) de baixa patogenicidade e 23 (25,5%) não patogênicas. Quando os resultados das classes de patogenicidade dos isolados foram associados à sensibilidade antimicrobiana, estirpes não patogênicas apresentaram menor sensibilidade ao antimicrobiano ampicilina e maior sensibilidade ao antimicrobiano estreptomicina, quando comparadas com as estirpes das demais classes de patogenicidade. Estirpes não patogênicas exibiram resistência a vários antimicrobianos, representando um alerta para a avicultura, uma vez que essas bactérias podem adquirir genes de virulência e, assim, infectar aves, outros animais e até mesmo o seres humanos.
Avaliação da patogenicidade in vivo e do perfil de resistência antimicrobiana de amostras de Escherichia coli isoladas de galinhas de postura comercial
Keywords: antimicrobial susceptibility; Escherichia coli; pathogenic; Sensibilidade antimicrobiana; Escherichia coli; patogenicidade